Key actors in community-driven social innovation in rural areas in the Nordic countries. (October 2020) - Jungsberg, Leneisja; Copus, Andrew; Herslund, Lise Byskov; Nilsson, Kjell; Perjo, Liisa; Randall, Linda; Berlina, Anna
Abstract: Rural areas in the Nordic countries often face challenges such as demographic change and the closure of public services. To address this situation, some rural communities have developed solutions which can be characterised as social innovation. This paper analyses 18 such community-driven social innovation projects across the Nordic countries and seeks to examine the importance of different actors in the initiation and implementation phases of such projects. Based on qualitative analysis, focusing on the different stages of community-driven social innovation, the paper assesses the importance of different actors in developing each of the projects. The analysis demonstrates the relative importance of community members, civil society organisations, the local public sector, the private sector, and regional and national authorities, in terms of their respective involvements in the initiation and implementation processes for these projects. The key findings from this paper emphasise the differences between initiation and implementation for each of these community-driven social innovation projects. The initiation phase is highly dependent upon community members, civil society organisations and the local public sector, whereas it is primarily civil society organisations which dominate the implementation phase. Central to initiating and sustaining community-driven projects is the capacity of local actors to develop ideas, to find resources and to manage decision-making. Highlights: Community-driven social innovation (SI) can be characterised by new models of collaboration across spaces and beyond the community level. Functional networks, upskilling in a supportive environment and community members banding together are crucial for SI. There is a shift in the involvement of actors from the initiation phase to the implementation phase in the SI process. Central to initiating and sustaining SI is the capacity of local actors to develop ideas, collect resources, and manage decision-making.